A Case Study on the Ayurvedic Management of Pratishyaya (Rhinitis) in Children Using Gojivhadi Syrup - Kalyani Aher; Gajanan Cheke; Karuna Ratnaparkhi (International Journal of Ayurveda and Pharma Research, 2025)
Pratishyaya, commonly correlated with allergic rhinitis in modern medicine, is a frequently encountered condition in children, often triggered by seasonal changes, environmental allergens, and compromised immunity. It presents with symptoms like sneezing, nasal discharge, nasal blockage, and headache, significantly affecting the child’s quality of life. Conventional treatments provide symptomatic relief but are often associated with side effects and recurrence. Ayurveda offers a holistic and safe approach through formulations that balance the Doshas, enhance immunity, and improve digestion. This case study evaluates the efficacy and safety of Gojivhadi Syrup, a classical Ayurvedic formulation, in the management of Vata-Kaphaja Pratishyaya in a 5-year-old male child with a history of recurrent rhinitis. The child presented with severe sneezing episodes (25–30/day), watery nasal discharge, nasal congestion, irritability, and disturbed sleep. Based on Ayurvedic principles and clinical examination, a diagnosis of Vata-Kaphaja Pratishyaya was made. The patient was administered Gojivhadi Syrup (5 ml thrice daily for 7 days). Significant clinical improvement was observed, with sneezing episodes reducing to 3–4/day, resolution of nasal congestion, and normalized laboratory parameters such as TLC, AEC, and ESR. No adverse effects were reported. The outcome suggests that Gojivhadi Syrup, with its Kapha-Vatahara, Deepana, Pachana, and Rasayana properties, can be a safe and effective remedy for allergic rhinitis in children. This case highlights the role of Ayurvedic management in pediatric respiratory disorders and encourages further research through large-scale clinical trials.